Direct effects of knowledge management practices on organizational performance (2020)
ABSTRACT: The relationship between knowledge management (KM) and firm performance is an interesting field for both scholars and practitioners. Despite the extant literature, more studies are required in order to clarify the abovementioned relationship. The purpose of this article is to examine the impact of KM practices on financial and nonfinancial performance. KM practices are knowledge creation practices, continuous learning practices (CLP), knowledge and feedback systems (KFS), and management of employees’ individual competencies. Methodologically the study uses partial least squares structural equation modeling. The results show that KFS affect firms’ financial performance and that CLP do not influence oneither financial or nonfinancial performance.